The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjopen-2020-047230
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and chronic rhinosinusitis with nasal polyps: a national population-based study

Abstract: ObjectivesWe performed a cross-sectional analysis of data from the nationwide Korea National Health and Nutrition Examination Survey to evaluate the association between obesity and chronic rhinosinusitis with nasal polyps (CRSwNP) or without nasal polyp (CRSsNP).DesignRetrospective cross-sectional analysis of health survey data.SettingVoluntary survey of representative South Korean populations.ParticipantsIn total, 32 384 individuals aged 19 years or older with available data on CRS and obesity were included.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…In greater depth, CRSwNP is reported in 40% of patients with severe asthma ( 4 , 5 ) and seems to be more prevalent in men ( 16 ) with no clear association with the presence of atopy ( 17 ). A recently published paper demonstrated the link between CRSwNP, asthma, and obesity ( 18 ), but we were not able to confirm these results. However, the retrospective nature of our study may have affected this outcome.…”
Section: Discussioncontrasting
confidence: 94%
“…In greater depth, CRSwNP is reported in 40% of patients with severe asthma ( 4 , 5 ) and seems to be more prevalent in men ( 16 ) with no clear association with the presence of atopy ( 17 ). A recently published paper demonstrated the link between CRSwNP, asthma, and obesity ( 18 ), but we were not able to confirm these results. However, the retrospective nature of our study may have affected this outcome.…”
Section: Discussioncontrasting
confidence: 94%
“…Male to female ratio was 1:1.6 in our study; there was female preponderance in all groups, with the difference between each of the experimental group (groups A, B, C, D, E) and control group (group F) being statistically insignificant (p-value = 0.34). This observation was consistent with study conducted by Nam J. S. et al (2021) [15]; however, Ahmed S. et al ( 2014) [16] showed male preponderance in their study. The difference in gender distribution from previous studies could be due to variation in demographic distribution from one population to other.…”
Section: Discussionsupporting
confidence: 92%
“…Factors linking the mucosal inflammation in CRS and asthma could be related to obesity and its potential to contribute to airway inflammation. Previous cross-sectional studies have demonstrated an association between obesity and CRS [ 14 16 ]. Nam et al investigated 32,384 individuals aged 19–86 years and, after performing a cross-sectional analysis, they found that the prevalence of CRS with nasal polyps was higher in subjects with obesity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cross-sectional studies have demonstrated an association between obesity and CRS [ 14 16 ]. Nam et al investigated 32,384 individuals aged 19–86 years and, after performing a cross-sectional analysis, they found that the prevalence of CRS with nasal polyps was higher in subjects with obesity [ 16 ]. Bhattacharyya conducted a cross-sectional analysis of a medical panel survey in the United States and found an adjusted odds ratio of 1.31 (1.18, 1.45) for CRS when obesity was present [ 14 ].…”
Section: Introductionmentioning
confidence: 99%